Current Outcome of Adjuvant Platinum-Based Chemotherapy for Nasopharyngeal Carcinoma: A Systematic Review - Namira Kesuma Jelita; Marlinda Adham; Saffanah Zahra (TALENTA PUBLISHER, 2020)
Introduction: Indonesia are among the top 5 countries with highest prevalence of NPC with a meta-analysis from 2018 stating prevalence as high as 13.084 cases. According to the latest guideline published by National Comprehensive Cancer Network (NCCN) in 2018. The main treatment for NPC remain radiotherapy, chemotherapy, and surgery. Induction or adjuvant chemotherapy place in treatment are still uncertain because variety of results from multiple clinical trial. Discussion: This review evaluates the current outcome of patient undergoing chemoradiotherapy with or without adjuvant chemotherapy and its usage in nasopharyngeal carcinoma patient. Search on online databases are performed with keywords including “nasopharyngeal carcinoma”, “chemotherapy”, “adjuvant” and “outcome” along with their synonyms. Studies in English from 2014-2019 are included. Quality assessment were done with Newcastle Ottawa Scale for Cohort studies and with CEBM for Randomized Controlled Trial Studies. Risk of bias assessed using Cochrane Method. A total of 7 studies were included in the final review with 1 RCT and 6 Cohort study. Most study have no significance in overall survival, progressive disease or distant metastasis free time, but differ in high stage and high risk patient. Three studies included toxicity as an outcome with adjuvant toxicity outweigh the need to add another round of chemotherapy. Conclusion: Adjuvant chemotherapy is believed to be necessary in eliminating residual cancer cells but current studies shows little improvement in overall survival and sometimes unbearable toxicities.